2020
DOI: 10.19026/ajfst.18.6041
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Moisture Content, Swelling, Opacity and Transparency with Addition Chitosan as Edible Films/Coating Base on Casein

Abstract: The objectives of this study was to characterize moisture content, swelling, opacity and transparency of casein solution addition chitosan as edible films/coatings.The effect of chitosan solutions on edible films/coating was chitosan solution 4% of the amount of casein solution. The thickness average value of the casein chitosan edible film is 0.076-0.087 mm. The EFC4 treatmentwas obtained in the lowest moisture content 29.24%, swelling degree 5.48% and opacity 0.078%. High moisture content in the edible film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
2
8
0
2
Order By: Relevance
“…Hence, the thickness of the CS/NaCas composite film was considered adequate [ 64 ]. The low moisture content and water solubility of the composite films could limit the growth of foodborne pathogens and prevent the disintegration of the edible films when in contact with high humidity or food products with high water activity [ 65 ]. Although the high opacity of CS/NaCas composite films limits the view of the food product, it offers protection for light-sensitive foods [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the thickness of the CS/NaCas composite film was considered adequate [ 64 ]. The low moisture content and water solubility of the composite films could limit the growth of foodborne pathogens and prevent the disintegration of the edible films when in contact with high humidity or food products with high water activity [ 65 ]. Although the high opacity of CS/NaCas composite films limits the view of the food product, it offers protection for light-sensitive foods [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biodegradable edible films with high water content are often susceptible to microbial growth due to the presence of nutritional components. 61 The recommended range for moisture content of bio-based edible films is approximately 16–24%. Hence, the moisture content of the composite film with nanoemulsified P. minor Huds.…”
Section: Resultsmentioning
confidence: 99%
“…60 Casein, a milk protein, has been explored as a base for edible lms and coatings due to its biodegradable and biocompatible nature. 61 A study by M. W. Apriliyani et al 62 investigated the properties of casein-based edible lms/coatings with the addition of chitosan. The study found that the thickness of the casein-chitosan edible lm ranged between 0.076 and 0.087 mm.…”
Section: Edible Packagingmentioning
confidence: 99%